Synthesis, characterization of hybrid nanocomposite material and fabrication of their advance membrane for removal of antibiotics from water - Fazal Suhrab Gul; Hayat Ullah; Ali Umar; Maliha Sarfraz; Muhammad Salman Khan; Misbah Ullah Khan; Muhammad Saleem Khan; Shifa Shafique; Lala Gurbanova; Abdul Wadood; Hanan A. Ogaly; Fatimah A. M. Al-Zahrani (PLoS ONE, 2025)
In this work, a selective membrane for antibiotics removal from water was fabricated. The ingredients utilized for membrane fabrication include functionalized TiO2 nanoparticles (NPs), poly methyl methacrylate (PMMA) and poly vinyl imidazole (PVIM). Firstly, TiO2 nanostructure’s surface was functionalized through APTES. The layer of functional monomers methyl methacrylate (MMA) and VIM (vinyl imidazole) was grafted onto TiO2 surface through controlled radical polymerization technique. The grafted material was fabricated into membrane with embedded selectivity utilizing molecular imprinting method. The material was diagnostically analyzed with Fourier Transform Infrared-Attenuated total reflection (FTIR-ATR) spectroscopy and NMR (Nuclear Magnetic Resonance) technique, which confirm functionalization of nanomaterial surface. The grafted layer around the nanoparticles was visualized with FESEM. The hybrid membrane shows excellent and promising results against removal of antibiotics from aqueous medium. The fabricated membranes via Molecular imprinted polymer (MIP) technique were applied for the selective removal of antibiotics (ciprofloxacin) from real water samples. The removal efficiency and selectivity of the hybrid membrane was monitored via UV visible spectroscopy.